2010
DOI: 10.1038/npp.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association of Galanin Polymorphisms with HPA-Axis Dysregulation, Symptom Severity, and Antidepressant Treatment Response

Abstract: Galanin (GAL) is an estrogen-inducible neuropeptide, highly expressed in brain regions reported to be involved in regulation of mood and anxiety. GAL possibly has a direct modulatory effect on hypothalamic-pituitary-adrenal (HPA)-axis regulation. Recent data from pharmacological and genetic studies indicate a significant function of GAL in stress-related disorders. By using a tag SNP approach covering the locus encoding preprogalanin (PPGAL), earlier findings of female-specific associations of polymorphisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 77 publications
5
32
0
Order By: Relevance
“…The GAL gene is widely expressed in the human brain [e.g., LC, forebrain, amygdala, and hypothalamus (26,51)], but its involvement in the development of depression is not well understood. Although previous studies indicated that it might have a sex-or estrogen-dependent effect (49), in our study the galanin system genetic variants significantly influenced the depressionrelated phenotypes both in males and in females, with similar magnitude of effect size, providing evidence that the excessive stress effect is not mediated by sex.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The GAL gene is widely expressed in the human brain [e.g., LC, forebrain, amygdala, and hypothalamus (26,51)], but its involvement in the development of depression is not well understood. Although previous studies indicated that it might have a sex-or estrogen-dependent effect (49), in our study the galanin system genetic variants significantly influenced the depressionrelated phenotypes both in males and in females, with similar magnitude of effect size, providing evidence that the excessive stress effect is not mediated by sex.…”
Section: Discussionsupporting
confidence: 47%
“…previous genetic studies on humans that the galanin system is involved in psychiatric disorders including alcoholism/addiction (43)(44)(45)(46)(47), panic disorder (48,49), and chronic pain-associated depression (50). Furthermore, recent functional studies provided the first evidence that polymorphisms in a highly conserved genetic region upstream from the GAL gene regulates GAL expression in brain areas, such as the amygdala and hypothalamus, implicated in the pathogenesis of depression (51,52).…”
mentioning
confidence: 99%
“…Furthermore, polymorphisms in and around the GAL gene have been associated with panic disorder and anxiety in female patients (Unschuld et al, 2008(Unschuld et al, , 2010. As a result of its expression in the amygdala (Miller et al, 1993b;Planas et al, 1994a) and its known role in mood modulation (Crawley et al, 2002;Hobson et al, 2006;Karlsson and Holmes, 2006;Madaan and Wilson, 2009;Paschos et al, 2009;Rotzinger et al, 2009), GAL and its three receptors have received a great deal of attention by researchers attempting to understand the role of the galaninergic system in chronic anxiety and depression and to develop novel therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In human studies, the sex-specific association of polymorphisms in the promoter region of the GAL gene in patients with anxiety disorder or major manic depression with the severity of anxiety symptoms, supports a role for galanin in the pathophysiology of clinical anxiety and depression and demonstrates the importance of sexand hormone-status-specific genetic associations (Unschuld et al, 2008(Unschuld et al, , 2010 (Table 6). Specifically, a meta-analysis of genome-wide association studies on over 10,000 individuals revealed a significant association between the GAL gene (rs2156464) and major depressive disorder (Wray et al, 2012).…”
Section: Genetic Association Studies Of Galanin and Galanin Recementioning
confidence: 99%